ANALYSIS OF FINANCIAL STATEMENTS AND ACCOUNTING TREATMENT OF ZAKAT AND INFAQ/SALAQAH PSAK 101 AND PSAK 109 - Sholeh, Hijrotus; Abdani, Fadlil (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
The application of PSAK 101 and PSAK 109 needs to be made for transparency. Transparency is very much needed for an amil entity in providing operational information, one way to be aware of transparency is through accountability reports, this will also attract the public to channel zakat and infaq/alms funds to LAZ Sidogiri. Thus, the more zakat and infaq/alms funds received, the greater the impact on the welfare of the people and the more poor people are assisted in meeting their needs. This research is a type of descriptive qualitative research. Analysis of the data used are observation, interviews, and documentation. The subjects of this research are the amil entity reports (PSAK 101) and the accounting treatment of zakat and infaq/alms (PSAK 1019) at LAZ Sidogiri. The results of this study show that in 2022 LAZ Sidogiri has implemented PSAK 109 for accounting treatment, from recognition and measurement, presentation, and disclosure and PSAK 101 for presentation of reports on amyl entities. However, LAZ Sidogiri does not present a cash flow statement and a report on changes in assets under management because there are no additional assets (zakat and infaq/alms funds) that have been deposited.